Effect of Filler Materials on Abrasive Wear Performance of Glass/Epoxy Composites - Bheemappa Suresha; Shivaprakash Vidyashree; Harshavardhan Bettegowda (Tribology in Industry, 2023)
When creating polymer-based composites, plain weave fabrics and micron-sized fillers offer bidirectional strength and reduced voids/inhomogeneity. In the present work, It was investigated how glass fabric reinforced epoxy composite (G-E) performed during three-body abrasive wear with and without ceramic fillers (SiO2, Al2O3, graphite, and fly ash cenospheres). In experiments, loads of 20 N and 40 N were applied at various abrading distances of 500 m, 1000 m, 1500 m, and 2000 m. According to the results of sand abrasive wear test, the specific wear rates of G-E based composites are sensitive to fibre and filler/matrix adhesion. Under all tribo-test settings, the SWR for all particulate G-E composites decreases in the following order: G-E > Gr/G-E > SiO2/G-E > Al2O3/G-E > fly ash cenosphere/G-E. Furthermore, the specific wear rate of the fly ash cenosphere filled G-E composites were found to be lower than the G-E and other filler materials filled G-E composites. There was 38.7% reduction in the specific wear rate at 40 N, 2000 m in fly ash cenosphere filled G-E composite. As per the evidence of scanning electron microscope images of worn-out surfaces, mechanisms such as ploughing, fibre breakage, fibre pull-out, fibre thinning, and a network of microcracks caused the wear in composites.